Malaria disrupts the rhesus macaque gut microbiome - Farinella, Danielle N.; Kaur, Sukhpreet; Tran, ViLinh; Cabrera-Mora, Monica; Joyner, Chester J.; Lapp, Stacey A.; Pakala, Suman B.; Nural, Mustafa V.; DeBarry, Jeremy D.; Kissinger, Jessica C.; Jones, Dean P.; Moreno, Alberto; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Previous studies have suggested that a relationship exists between severity and transmissibility of malaria and variations in the gut microbiome, yet only limited information exists on the temporal dynamics of the gut microbial community during a malarial infection. Here, using a rhesus macaque model of relapsing malaria, we investigate how malaria affects the gut microbiome. In this study, we performed 16S sequencing on DNA isolated from rectal swabs of rhesus macaques over the course of an experimental malarial infection with Plasmodium cynomolgi and analyzed gut bacterial taxa abundance across primary and relapsing infections. We also performed metabolomics on blood plasma from the animals at the same timepoints and investigated changes in metabolic pathways over time. Members of Proteobacteria (family Helicobacteraceae) increased dramatically in relative abundance in the animal’s gut microbiome during peak infection while Firmicutes (family Lactobacillaceae and Ruminococcaceae), Bacteroidetes (family Prevotellaceae) and Spirochaetes amongst others decreased compared to baseline levels. Alpha diversity metrics indicated decreased microbiome diversity at the peak of parasitemia, followed by restoration of diversity post-treatment. Comparison with healthy subjects suggested that the rectal microbiome during acute malaria is enriched with commensal bacteria typically found in the healthy animal’s mucosa. Significant changes in the tryptophan-kynurenine immunomodulatory pathway were detected at peak infection with P. cynomolgi, a finding that has been described previously in the context of P. vivax infections in humans. During relapses, which have been shown to be associated with less inflammation and clinical severity, we observed minimal disruption to the gut microbiome, despite parasites being present. Altogether, these data suggest that the metabolic shift occurring during acute infection is associated with a concomitant shift in the gut microbiome, which is reversed post-treatment.